The facilities of detection by using a tool of Wireshark - Sarah R. Hashim; Rusul A. Enad; Alyaa M. Al-khafagi; Noor Kamil Abdalhameed (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Wireshark is easy for using as a packet inspection tool, in additional the feature of packets colorizing is easy for a various type of traffic. This paper exemplifies how Wireshark is used in networks as a tool. To clarify the effectiveness of malicious packet identification in any network, an experiment was conducted. Using the Wireshark program, testing was carried out in real time through experimentation and analysis. Inferences were drawn that clearly show Wireshark's capabilities as a tool in a powerful system for discovering the breach. The functionality of Wireshark is to analyze the network protocol and its open-source features for enabling the addition of likely tasks in the detecting devices were emphasized. Wireshark's skills for handling and interpreting packet data have been highlighted and the access control list (ACL) filtering has been the main application of Wireshark.